Corporate governance attributes, banks characteristics and green banking disclosure in Indonesia - Yulia Yulia; Muhammad Rafiuddin; Rokiah Paee (Universitas Islam Negeri Walisongo Semarang, 2025)
Purpose - The purpose of this study is to examine the influence of corporate governance attributes and banks characteristic on Green Banking Disclosure of Indonesian Islamic banks. Method - Using the panel data regression framework of multiple linier regression method, this study analyses a sample comprising nine Indonesian Islamic banks from 2018 to 2024. Result - The results show that board size, independent ommissioner, profitability, and size have a significantly positive effect on Green Banking Disclosure Index (GBDI), while sharia supervisory board has significantly negative on GBDI but contradictive to board gender diversity, meeting frequency, and leverage do not have significantly affect on GBDI. Implication - The practical implications of this study emphasize the critical role of corporate governance attributes and banks characteristic in improving green banking disclosure index of Indonesian Islamic banks. Originality - This study comprises an in-depth examination of corporate governance attributes and banks' characteristics, as there is limited literature in Indonesia concerning diversity on the board and banks' characteristics, despite the relevance of the topic.